Institutions and properties of the transaction: influences on land rental contract design in Poland - Annette Hurrelmann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2005)
The article analyses influences on the design of land rental contracts in Poland. Attention is paid to the effect of both the properties of the transaction as identified in Transaction Cost Economics (asset-specificity, uncertainty, frequency) and the features of the institutional environment (legal as well as customary rules) as studied by the Economics of Property Rights. The conclusion is that institutional influences have a very strong effect and should not be disregarded in the explanation of contract choice.
Keywords: 330; Bodenmarkt; Miete; Mietrecht; Transaktionskosten; Institutionelle Infrastruktur; Polen